Prevalence of Type 2 Diabetes Mellitus in patients with Chronic Liver Disease (Journal of Medicine, 2017)
Background and Purpose: The development of type 2 diabetes mellitus (T2DM) is caused by a combination of genetic factors and lifestyle factors like obesity, lack of physical activity and stress. T2DM can develop in chronic liver disease (CLD) though its actual mechanism is not fully understood. In case of hepatitis B virus (HBV) related CLD, HBV infection has been directly related to development of abnormal glucose metabolism by pancreatic islets cell injury. Development of Insulin resistance in case of hepatitis C virus (HCV) is the key pathogenesis of development of type 2 diabetes. We aimed to study the magnitude of the problem of T2DM among the patients with various types of CLD and to find out the association of diabetes mellitus with the demographic and clinical characteristics of the patient admitted in Medicine ward in Dhaka Medical College Hospital.Methods: This was an observational cross sectional study of 60 patients admitted into department of Medicine, Dhaka Medical college hospital between June, 2013 to December, 2013. It included all patients ?18 years of age and admitted with CLD. A diagnosis of CLD was made clinically by any 2 stigmata of liver disease and biochemical, ultrasonographic, endoscopic evidence of esophageal varices ± liver biopsy.Results: Of the total 60 CLD patients, 40 (66.7%) suffered from chronic HBV infection, 11 (18.3%) chronic HCV infection and alcoholic liver disease 5 (8.3%), Autoimmune 1 (1.7%), Wilson disease 1 (1.7%) and unknown cause were 2 (3.3%). Among the study subjects 21.67% had overt Diabetes Mellitus and it was found to be highest among those with chronic hepatitis C (36.4%) and those with chronic hepatitis B (20%) alcohol (20%). Type 2 DM was significantly higher among the CLD patients aged more than 50 years or more.Conclusions: It can be concluded that the occurrence of diabetes and impaired glucose tolerance (IGT) could be a matter of great concern in CLD patients, indicating towards the need for regular monitoring of the glycemic status in these patients, which would have a definite role upon the treatment strategy.J MEDICINE July 2017; 18 (2) : 68-74